Changes in litter quality caused by simulated nitrogen deposition reinforce the N‐induced suppression of litter decay. Issue 10 (29th October 2015) - van Diepen, Linda T. A.; Frey, Serita D.; Sthultz, Christopher M.; Morrison, Eric W.; Minocha, Rakesh; Pringle, Anne
Abstract : Rates of nitrogen (N) deposition are increasing in industrialized and rapidly developing nations. Simulated N deposition suppresses plant litter decay rates, in particular for low quality (high lignin) litter. Litter quality is a primary driver of litter decomposition; however, it is not clear how changes in litter quality caused by long‐term ecosystem exposure to chronic N additions interact with altered soil N‐availability to influence litter decay dynamics. To document the effects of simulated N deposition on litter quality, we conducted a meta‐analysis of available litter nutrient data from simulated N deposition experiments in temperate forests. To directly test whether changes in litter quality caused by N deposition affect decay rates, we also conducted a reciprocal litterbag study in an existing N addition experiment, where a northern hardwood forest has been exposed to simulated N deposition for more than 20 years. The experiment enabled us to disentangle the effects of N additions, litter quality, and their interactions on litter decay dynamics. We measured litter mass loss and extracellular enzyme activities after one and two years of decomposition. The meta‐analysis demonstrated that simulated N deposition causes decreases of leaf Al, B, Ca, Mg, Mn, P, and Zn concentrations, and increased leaf N concentrations. Moreover, higher cumulative amounts of simulated N deposition result in greater decreases of leaf Ca and Mn concentrations. In the field experiment, litter originally collected from N‐enriched plots exhibited similar N‐induced nutrient changes as observed in our meta‐analysis and also had lower lignolytic enzyme activities and decay rates than litter collected from control plots. The decreased litter decay rates observed with simulated N deposition were a result of the combined effects of the N fertilization itself and the historical effects of N deposition on tree litter chemistry. The data suggest that changes in litter quality caused directly by long‐term N enrichment reinforce the negative effects of simulated N deposition on litter decay, particularly for high lignin species. The slowed decay associated with changes in litter quality caused by N enrichment itself may partly explain the accumulation of organic matter previously observed at ours and at other simulated N deposition experiments.